IEEE INFOCOM 2022 - IEEE Conference on Computer Communications Workshops (INFOCOM WKSHPS) 2022
DOI: 10.1109/infocomwkshps54753.2022.9798350
|View full text |Cite
|
Sign up to set email alerts
|

Latency-aware C-ITS application for improving the road safety with CAM messages on the Smart Highway testbed

Abstract: The Cooperative Intelligent Transportation System (C-ITS) testbed or simplified called the Smart Highway (Antwerp, Belgium) is designed to facilitate research in the area of distributed/edge computing and vehicular communications. The Smart Highway testbed deploys the Cooperative Awareness Basic Service to exchange Cooperative Awareness Messages (CAMs) between road C-ITS entities, e.g., C-ITS vehicles and Road-Side Units (RSUs). CAMs support vehicular safety and traffic efficiency applications by providing the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…As being shown in Figure 2, primarily ITS-G5 is a good fit to compare its performances against the cellular approach. Charpentier et al concluded similar results for the performance of CAM messages for his experimental evaluation between the technologies ITS-G5 and LTE-V2X PC5 [13]. With the average latency performance results of a single RSU and single OBU standing still next to each other in hand, we will move to a more realistic experimental setup using a moving vehicle over the Smart Highway.…”
Section: A Single Rsu Non-moving Resultsmentioning
confidence: 61%
“…As being shown in Figure 2, primarily ITS-G5 is a good fit to compare its performances against the cellular approach. Charpentier et al concluded similar results for the performance of CAM messages for his experimental evaluation between the technologies ITS-G5 and LTE-V2X PC5 [13]. With the average latency performance results of a single RSU and single OBU standing still next to each other in hand, we will move to a more realistic experimental setup using a moving vehicle over the Smart Highway.…”
Section: A Single Rsu Non-moving Resultsmentioning
confidence: 61%
“…This forms already a first challenge to the vision where all different (vendor crossing) UAVs can speak and understand the same language. Moreover, recent research performed by Charpentier et al, proofed that ITS-G5 (IEEE 802.11p) and LTE-V2X (3GPP) do not meet the requirements for UAVs [3]. Which reconfirms that ITS-G5 and LTE-V2X are designed for basic safety and traffic management use cases i.e., to support basic cooperative active traffic safety, traffic management, and telematics applications and thus not for advanced UAV communication [11,16].…”
Section: Current Major Communication Technologiesmentioning
confidence: 99%
“…There has been a tremendous amount of work focusing on VANETs utilizing IEEE 802.11p, the default standard for distributed V2V communications. The IEEE 802.11p standard is a contention-based MAC protocol method using carrier-sense multiple access with collision avoidance (CSMA/CA) to avoid interference and collisions between different nodes [18][19][20].…”
Section: Introductionmentioning
confidence: 99%